Determinasi Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Melalui Kepercayaan - Dedek Kurniawan Gultom; Muhammad Arif; Muhammad Fahmi (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
This study aims to analyze the effect of customer satisfaction on customer trust, the effect of customer satisfaction on customer loyalty, the effect of trust in customer loyalty and analyze the indirect influence of customer satisfaction on customer loyalty through trust in Starred Hotels in Medan. The approach used in this study was an associative approach. Data collection techniques used are interviews, questionnaire and study documentation. The sampling technique was a non-probability sampling technique. While the sample in the study were 150 hotel customers. The data analysis technique uses path analysis. The results show that customer satisfaction has a positive and significant effect on customer trust, customer satisfaction also has a positive and significant effect on customer loyalty, customer trust has a positive and significant effect on customer loyalty. The role of customer trust significantly mediates the influence of customer satisfaction on customer loyalty of Starred Hotels in Medan.